620.CAD MODELLING OF PARALLEL ROBOT (TRIPOD) IN MATLAB/SIMULINK - Maja, Anackova; Hristijan, Mickoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The purpose of this paper is to create a model simulation of a parallel robot with PID controller using the programming package Matlab/ Simulink. In this paper, forward and inverse kinematics of parallel robot tripod is presented; model of the parallel robot in the programming package Solid Works is constructed; simulation model of the parallel robot tripod is made by conversion from Solid Works to Matlab/Simulink and results for velocities and accelerations in its kinematic joints are obtained that serve to the management and control of the mobile platform as a major problem in the construction of a parallel robot. Model simulation of parallel robot will be the basis for creating models of parallel robots with more complex structure, detailed understanding of their kinematics and control design as an inevitable part of the future of robotics and mechatronic.